The development and application of a mobile-based data collection system for a growth monitoring programme in selected primary care centres in the Republic of Mauritius - Ana Irache; Raveena Murachpersad; Rishi Caleyachetty (BMJ Global Health)
There is increased interest in child nutrition globally which has resulted in high-level commitments to address child malnutrition. However, monitoring these commitments are hindered by non-existent or weak paper-based child nutrition surveillance systems. We describe the development and application of a mobile-based data collection system in near real-time for children aged 0–5 years attending government growth monitoring sessions in selected primary care centres in the Republic of Mauritius. The mobile-based data collection form was designed using KoBoToolbox and was used in the growth monitoring programme across two districts in the north of the country. We observed nine primary care centres over a period of 18 days and collected routine data on weight from 576 children. A short questionnaire and interviews were conducted with a member of healthcare staff involved in the growth monitoring programme to measure the usability and explore the perceptions of an electronic data collection form. Prevalence estimates of child underweight and overweight were also calculated. Eight out of 10 (80%) participants obtained a System Usability Scale score >80. Healthcare staff believed that the mobile-based form had the potential to reduce their workload and reduce data transmission time. An important deployment-related issue was the need for adequate training in the use of a mobile device to collect nutrition surveillance data. Overall, 5.5% (95% CI 3.9% to 7.7%) of children were underweight and 4.4% (95% CI 3.0% to 6.5%) were overweight. Through the development and implementation of this mobile-based data collection system, we have shown the value and potential usability for mobile technologies to strengthen the child nutrition surveillance system in the Republic of Mauritius.